Leopoldia buseana (Asparagaceae, Scilloideae), a new species from southwestern Anatolia - Yildirim, Hasan; Akbaş, Kenan; Özdöl, Tuğkan (Phytotaxa, 2023)
Leopoldia buseana Yıldırım (Asparagaceae) is described as a new species to science. It is endemic to the western Anatolia region of Türkiye. Leopoldia buseana is only known from Muğla Province. The new species is morphologically similar to L. muglaensis, L. elmasii, and L. weissii. Diagnostic morphological characters are discussed and compared with those related taxa. Leopoldia buseana is easily distinguished from related species by its distinctly longer inflorescence, the number of fertile and sterile flowers, mauve to bluish-mauve buds and early stage of fertile flowers, flat or sometimes slightly channeled and broader leaves, and the seed surface ornamentation. Diagnostic characters, a comprehensive description, photographs, and a distribution map are provided.